Hubungan Kecerdasan Emosional dengan Turnover Intention - Mumun Surahman (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
Emotional intelligence plays a significant role in the workplace for investigating organizational behavior and social psychology because possessing emotional intelligence enables an individual to understand and attend to their own emotions, facilitating their interactions with colleagues to work together towards common goals. This study aims to analyze the relationship between emotional intelligence and turnover intention. The research methodology employs a quantitative approach with a sample size of 171 employees from BRI in Ciamis Regency and Banjar City. Data collection was conducted using a questionnaire and subsequently analyzed through simple regression. The research findings indicate a correlation between emotional intelligence and turnover intention.